Comparison of the effects of administration and non-administration of antibiotics on post-surgical complications of impacted wisdom teeth - Mozhgan Kazemian; Saleh Dadmehr (Tehran University of Medical Sciences, 2020)
Background and Aims: Some of the post-operative complications of impacted third molar surgery, one of the most prevalent surgeries in oral field, are known to be infection, erythema, trismus and pain. Antibiotic prescription to prevent post-operative infection under some particular circumstances, is acceptable but under debate considering their disadvantages. In the present study, we examined the infection rate in patients taking no or 2 types of antibiotics distinctively after impacted mandibular third molar surgery. Materials and Methods: In this double blind clinical trial, 90 patients within the age range of 18 to 34 were dedicated to 3 groups (group 1: 2 capsules of placebo on surgery day and 1 for 4 days, group 2: Amoxicillin 500 mg every 8 hours for 5 days, group 3: Azithromycin 250 mg, 2 capsules on surgery day and 1 capsule for 4 days). All subjects were treated by a sole surgeon, protocol, surgical technique, and flap type and the same amount of osteotomy. In addition to aforesaid drugs, the patients received chlorhexidine and Gelofen 400 mg. At the day 7 postoperative, cases were examined to evaluate the infection (trismus, erythema and halitosis). Data were analysed using Chi-Square test and the groups were compared by Kruskal-Wallis test. Results: Three signs of infection (halitosis, erythema and trismus) were compared in patients. Symptoms of halitosis and erythema were more indicated in first group, but the ultimate statistical analyses among the 3 groups from halitosis and erythema viewpoint showed no significant difference (P=0.072, P=0.149). Although, no severe trismus was reported, the most moderate trismus incidence was in group 2 and mild trismus was exhibited in group 1. In group 3, no trismus occurred. On the whole, the trismus frequency among groups was statistically significant (P=0.004). Conclusion: Comparing infection symptoms of the three study groups emphasized the fact that only trismus rate was statistically significant (P=0.004). On balance, the results of this study indicated that antibiotics did not have significant impact on the reduction of most postoperative complications, especially on infection.